Analysis of Students' Computational Thinking Processes in Merdeka Curriculum Differentiation Learning using The Open-Ended Problem Based Learning Model - Santika Lya Diah Pramesti; Heni Lilia Dewi; Norma Alias (Hipotenusa: Journal of Mathematical Society, 2024)
This research aims to evaluate the effect of implementing differentiated learning using the Open-Ended Problem Based Learning model on students' computational thinking abilities at the Batang State Tsanawiyah Madrasah. The research used mixed methods with a concurrent embedded model, which combines quantitative and qualitative approaches. Data was collected through computational thinking ability tests, interviews, and observations during the research period. The research results show a significant increase in students' computational thinking abilities after implementing differentiated learning. Quantitative data analysis shows significant differences between before and after learning, with visible improvements in aspects of computational thinking capabilities such as abstraction, algorithms, decomposition, and pattern recognition. These findings show that differentiated learning using the Open-Ended Problem Based Learning model can improve students' abilities in computational thinking and solving problems effectively.